Geochemical characteristics, palaeoenvironment, and provenance of marine mudstone in Shanxi Formation of Huaibei Coalfield, southern North China Plate. (1st February 2021) - Li, Jun; Gui, Herong; Chen, Luwang; Fang, Pei; Li, Guangping; Li, Ruirui
Abstract : During the Permian period of the southern China North Plate, a layer of marine mudstone (source rock) with oil and gas potential has been widely deposited, with a thickness of about 10.4 m, but their formation mechanism remains unclear. Here, through the application of various analysis techniques, the mineral composition of the mudstone and a series of related geochemical data are obtained to investigate their sedimentary environment and tectonic setting. Mineral composition analysis describes that marine mudstone is mainly composed of quartz, illite, kaolinite, montmorillonite, and other silicate minerals, while carbonate components such as calcite are rare. Meanwhile, the higher content of clay minerals promoted the organic matter during the deposition period enrichment. Indicators and diagrams (i.e., chemical index of alteration [CIA] [> 80], index of compositional variability [ICV] [ 0.6], A‐CN‐K, Th/Sr vs. Zr/Sr) reveal that marine mudstone was deposited for the first time under strong weathering. Some trace element ratios and redox elements provide evidence that in warm and arid climates, mudstones are deposited under oxic‐anoxic conditions based on the participation of seawater, which is consistent with the conclusion of palaeomagnetics. The binary discriminant diagrams of Al2 O3 versus TiO2, Hf‐La/Th versus Ni‐TiO2 suggest that the marine mudstone parent rock is felsic igneous rock, and the lithology may be granite. Combining the regional structural evolution and the direction of transgression during the sedimentary period, it is speculated that the provenance of marine mudstone is the North Qinling tectonic belt in the southwest of the study area and the Yinshan ancient land in the north. Abstract : Shanxi period (Early Permian) seawater centre is located in the study area and Huainan area, and the transgression direction is mainly southeast to northwest. The maximum range of marine mudstone line roughly represents the maximum transgression boundary in Shanxi period.